Plan de marketing para el posicionamiento de la empresa industrial de alimentos Cordovez Quecor cia. ltda. en la provincia de Pichincha, cantón Mejía, parroquia Alóag, período 2014-2017 - Arias Benalcázar, Diana Carolina (2016)
For the development of this research work it was raised as a goal: To design a marketing plan that allow to increase the position of the "Quecor" company to its respective development a situational analysis of the company in order to know the current situation was carried out, that is facing it and thus to correct and leverage the strengths, weaknesses, threats and opportunities, through this study it was concluded that the main problem of the company is the low position it has on the market. The methodology used was; deductive, analytical and statistical method which consisted of obtaining results through techniques and research tools such as: survey, interview, questionnaire, and it was possible to verify that the company requires mix de marketing strategies which are product strategies, price, place, promotion and advertising that will increase the recognition in the parish. The design of each of these strategies aims to increase the level of market positioning of the "Quecor” dairy company and thus to know the customers‟ tastes and preferences.